Comparative Study of Competency and Certification of Special Education Teachers in Indonesia and Another Various Country - Fildzah, Yumna Nur (The Center for Disability Studies and Services Brawijaya University, 2020)
The teacher is a professional teaching profession with the main responsibility of educating, teaching, guiding, directing, training, assessing, and understanding students. Teachers are the main pillars in ensuring the quality of education in each country. Therefore teachers are required to be professional by fulfilling certain competencies and getting recognition as educators through teacher certification. Educator certificates given to teachers who have fullfill professional teacher standards, referred to through teacher certification, can be understood teacher eligibility in relation to learning agents who can realize the goals of national education. Knowing the importance of creating a professional teacher, so the writer will explain about the competencies and certification systems of special education teachers that developed in Indonesia, Germany, Norway, Singapore, the United Kingdom, and the Netherlands. Through this consideration, it can be seen differences of opinion and differences in systems that can be used to be considered in improving the quality of national education. The research method used is descriptive qualitative method by describing the conditions relating to the competence and certification systems of special education teachers in several countries. Data collection techniques using document review.